Prevalence of Complications in Laparoscopic Cholecystectomy in Extracting Gallbladder by Using Supra-Umbilical Port Versus Epigastric Port in Sulaimani Teaching Hospital: A Prospective Case Series Study - Hiwa Ahmed; ALI Rashid (مجلة الكوفة الطبية)
Background: Depending on the surgeon's preference, different locations for trocar incision can be used to extract the gallbladder. Some studies are claiming that epigastric port is better for retrieval due to easiness for the surgeon as there is no need to change the position of the telescope and readjustment of the surgeon’s position. Other studies show the superiority of umbilical port in terms of pain.